Emerging Roles of Impaired Autophagy in Fatty Liver Disease and Hepatocellular Carcinoma - Suryakant Niture; Minghui Lin; Leslimar Rios-Colon; Qi Qi; John T. Moore; Deepak Kumar (International Journal of Hepatology)
Autophagy is a conserved catabolic process that eliminates dysfunctional cytosolic biomolecules through vacuole-mediated sequestration and lysosomal degradation. Although the molecular mechanisms that regulate autophagy are not fully understood, recent work indicates that dysfunctional/impaired autophagic functions are associated with the development and progression of nonalcoholic fatty liver disease (NAFLD), alcoholic fatty liver disease (AFLD), and hepatocellular carcinoma (HCC). Autophagy prevents NAFLD and AFLD progression through enhanced lipid catabolism and decreasing hepatic steatosis, which is characterized by the accumulation of triglycerides and increased inflammation. However, as both diseases progress, autophagy can become impaired leading to exacerbation of both pathological conditions and progression into HCC. Due to the significance of impaired autophagy in these diseases, there is increased interest in studying pathways and targets involved in maintaining efficient autophagic functions as potential therapeutic targets. In this review, we summarize how impaired autophagy affects liver function and contributes to NAFLD, AFLD, and HCC progression. We will also explore how recent discoveries could provide novel therapeutic opportunities to effectively treat these diseases.